Analysis of excess pore pressure evolution during and following excavation and piling in soft clay - Lundqvist, Viktor; Sylvén Stålhandske, Annie (My University, 2024)
This thesis aims to study the combined impact of pile driving and excavation have on the development and evolution of excess pore pressure, heave, and heave pres sure. To fulfill this aim, numerical analyses were conducted to simulate the pore pressure evolution and heave during pile driving and excavation processes. Two constitutive models were used, a Mohr-Coulomb model and the Modified Cam Clay model. Two numerical models were first constructed simulating excavating and pil ing respectively, where a cavity expansion was used to simulate the pile installation. The results from these models were validated against analytical solutions found in the literature to verify that the pile driving and unloading, yielded results that were consistent with theory. After these models had been validated, a new model sim ulating both excavating and piling was constructed. The computed results from this model were compared to monitored pore pressure data from an existing con struction site, located in Gothenburg, Sweden. Thereafter, a parametric study was conducted to generalise the result by varying the permeability and stiffness. The results indicate that piling before excavating reduces the heave pressure, compared to only excavating. Furthermore, results also indicate that piling before excavating, generates less vertical displacements at the excavation bottom, compared to to the reverse construction sequence (i.e piling after excavating). As the piling model in this thesis only simulated the cavity expansion and not the pile material, the reinforcing effect piles have on heave would be of interest to study in future research. Further research could also analyse the effect of a group of piles, with regard to pore pressure, heave and heave pressure.
Keywords: Heave pressure; Unloading; Excavation; Piling; Pore pressure; Cavity expansion; Numerical modeling; Mohr-Coulomb; Modified Cam Clay